Inhalation Risk Assessment of Thinner Use in Furniture Painting Workers at Furniture X - Kumara, Dimas Bayu Putra; Fairuzahra, Alifia; Herlinawati, Aprilia; Riandini, Aurellia Risma; Haidar, Muhammad Rafli; Dwiyandari, Fransiska; Simbiak, Ruth Grace Insos (Journal of Safety Education, 2025)
The safety and health of workers in the furniture painting industry are a primary concern, given the increasing use of hazardous chemicals that can lead to various health issues. This study aims to analyze the inhalation risk associated with thinner use among furniture painting workers at Furniture X. Using a descriptive research method; the analysis focuses on inhalation exposure risks linked to thinner chemicals. Data were collected through a review of thinner Safety Data Sheets (SDS), field observations, and structured interviews, with the findings assessed using the Chemical Health Risk Assessment (CHRA) framework. The assessment considered Hazard Rating (HR), Exposure Rating (ER), and Risk Rating (RR) factors. The results indicate that thinner, which is mixed with paint for the painting process, contains chemicals such as toluene (CAS: 108-88-3), xylene (CAS: 1330-20-7), and acetone (CAS: 67-64-1), each with varying levels of risk (RR). One of the substances in thinner, xylene, was identified as having significant potential to cause respiratory irritation. The study concludes that the CHRA method applied to the furniture painting process at Furniture X revealed three hazardous chemicals in the thinner used, with xylene posing a notable health risk. These findings underscore the need to implement safe work procedures and ensure the appropriate use of personal protective equipment (PPE).